The utilization of Indonesia soft power: promoting Toba Caldera as UNESCO global geopark 2020/ Hendra Manurung and Elvinro Sinabariba - Manurung, Hendra; Sinabariba, Elvinro (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2021)
The goal of this project is to provide an analytical description of Toba Caldera's potential to become a UNESCO Global Geopark by 2020. The research employed qualitative methods and was carried out through a review of the literature. Journals, government papers, news media, and the internet were all utilised as sources of supporting information. There are interconnections between Indonesia soft powers and the ongoing contributions of stakeholders in the Toba Caldera Promotion Project, which is intended to assist sustainable tourist growth. Toba Caldera is a popular tourist attraction across the world since it is home to 13 geo-sites that offer breath-taking views. According to the findings of this study, Toba Caldera's international fame will likely result in an increase in incoming tourist arrivals.